Critical moment for Indonesian journalism: disappearance of journalistic firewall - Nanang Krisdinanto; Merlina Maria Barbara Apul; Rajab Ritonga (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to understand the dynamics of journalists’ professionalism regarding the critical moment for Indonesian journalism in carrying out their journalistic practices. This study uses a qualitative approach with a case study method and took place in Surabaya, East Java, the second largest city in Indonesia that records the highest media growth in the country besides Jakarta and Medan. The results of this study show that there has been the destuction of old journalistic values including journalistic independence and the normalization of new journalistic practices that mix editorial and business among journalists surveyed. Nowadays, the mixture is considered a normal journalistic practice. The COVID-19 pandemic has accelerated the process of eroding journalists’ welfare and reviving pre-pandemic unethical practices, such as bribery, extortion and news withdrawal on the pretext of welfare. The pandemic has also given rise to a turning point in journalistic practices related to the press business model which traditionally relied on ads and changed the direction of news reporting that the journalistic firewall has cordoned by separating editorial from business. This gave rise to the destruction of journalistic values including independence and the disappearance of the journalistic firewall.